Novel Microstructural Features on Heat and Mass Transfer in Peristaltic Flow Through a Curved Channel - Raheel Ahmed; Nasir Ali; Sami Ullah Khan; A. M. Rashad; Hossam A. Nabwey; Hossam A. Nabwey; Iskander Tlili; Iskander Tlili (Frontiers in Physics, 2020)
Recently, significant interest has been developed by researchers toward the peristaltic transport of fluid, as this phenomenon involves a variety of applications in the biomechanics, bioengineering, and biomedical industries. In the present contribution, we investigate the effect of heat and mass transfer on magnetically influenced micropolar flow induced by peristaltic waves. The fundamental laws regarding current flow problem are employed by using curvilinear coordinates. A reduction of these equations is made based on lubrication approximation. The solution algorithm is based on the implementation of the famous finite difference method. The fundamental impacts of coupling number, micropolar parameter, Hartmann number, Brinkman number, rate of chemical reaction, and curvature parameter on longitudinal velocity, pressure rise, temperature, and mass concentration are analyzed in detail. The flow patterns in the channel illustrating the effects of several involved parameters are also displayed.